DNA binding, topoisomerase inhibition and cytotoxicity of palladium(II) complexes with 1,10-phenanthroline and thioureas - Barra, Carolina V. [UNESP]; Rocha, Fillipe V.; Morel, Laurent; Gautier, Arnaud; Garrido, Saulo S. [UNESP]; Mauro, Antonio E. [UNESP]; Frem, Regina C.G. [UNESP]; Netto, Adelino V.G. [UNESP] (Elsevier, 2016)
Metallointercalators represent a promising alternative in cancer chemotherapy. We present herein DNA binding, topoisomerase inhibition and cytotoxic studies on a series of complexes of general formulae [Pd(phen)(tu∗)2]2+ incorporating the intercalator 1,10-phenanthroline and thiourea ligands (L = thiourea 1, N-methylthiourea 2, N,N′-dimethylthiourea 3). DNA-unwinding results showed that the complexes can induce the unwinding of the plasmid DNA. The binding constants (Kb) for the interaction of the complexes with SS-DNA were determined by UV spectroscopy. Competitive experiments with ethidium bromide (EB) were investigated by fluorescence spectroscopy and show that all the complexes were able to displace EB from the DNA-EB complex. The results suggest that they may interact with DNA by intercalation. Compounds were tested against human oral carcinoma cell line (KB), human breast cancer cell line (MCF7) and cisplatin-resistant human breast cancer cell line (MCF7-R) and showed good cytotoxic activity towards MCF7-R. Compounds 2 and 3 were also able to cause topo II inhibition.
Keywords: Cytotoxicity; DNA binding; Metallointercalator; Palladium(II); Thioureas; Topoisomerase inhibitors